An updated meta-analysis evaluating limb management after total knee arthroplasty—what is the optimal method? - Hai-yang Wang; Guang-shu Yu; Jie-hui Li; Shou-xiong Zhang; Yan-bin Lin (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Purpose Postoperative knee flexion protocol has been widely recognized as a highly attractive, simple, and cost-effective tactic to improve patient’s outcomes after primary total knee arthroplasty (TKA). However, optimal knee position and duration of knee flexion are still controversial. The purpose of this meta-analysis was to compare the effectiveness of different postoperative knee flexion protocols, as an aid to find out optimal limb management strategy following TKA. Methods We conducted a meta-analysis to identify the available and relevant randomized controlled trials (RCTs) with regard to the influence of different postoperative knee positions on clinical outcomes after primary TKA in electronic databases, including PubMed, EMBASE, the Cochrane Library, Web of Science, CNKI, Wanfang Med Online, and VIP, up to May 2018. In this meta-analysis, three major subgroups based on diverse postoperative knee flexion protocols were considered: long-term (≥ 24 h) high flexion (> 30°), short term (< 24 h) high flexion (> 30°), and long-term (≥ 24 h) mild flexion (≤ 30°). The statistical analysis was performed using the Review Manager (RevMan) version 5.3 software. Results A total of 16 trials were finally included in this meta-analysis. The result of subgroup analysis indicated that keeping the knee in high flexion (> 30°) postoperatively for a long time (≥ 24 h) significantly reduced total blood loss (P < 0.00001), hidden blood loss (P < 0.00001), and transfusion requirements (P = 0.003) and led to a significant improvement in range of motion (ROM) at 1 week after operation (P < 0.00001); keeping the knee in high flexion (> 30°) postoperatively for a short time (< 24 h) significantly reduced total blood loss (P = 0.006) and hidden blood loss (P < 0.00001) but not significantly improved ROM at 1 week after operation (P = 0.34) and reduced transfusion requirements (P = 0.62); and keeping the knee in mild flexion (≤ 30°) postoperatively for a long time (≥ 24 h) significantly reduced total blood loss (P = 0.02) and transfusion requirements (P = 0.02) and improved ROM at 1 week after operation (P < 0.00001) but not significantly reduced hidden blood loss (P = 0.11). Furthermore, there was no significant difference with respect to the rates of wound-related infection and DVT between the three knee flexion subgroups. Conclusions This meta-analysis showed that the long-term (≥ 24 h) high flexion (> 30°) protocol could be an optimal limb management to reduce blood loss and blood transfusion requirements and facilitate early postoperative rehabilitation exercises in patients after primary TKA without increasing in complication rate.